Epidemiology and the Histopathological Pattern of Diagnosis of Thyroid Diseases in a University Hospital in Riyadh, Saudi Arabia - Emad, Raddaoui; Shaesta, Naseem Zaidi (Journal of Hematology and Oncology Research, 2015)
Background/Aims: Thyroid disorders are a common, worldwide clinical problem in general practice.It presents predominantly as a thyroid nodule. Each thyroid nodule has a risk of cancer. The incidence of thyroid cancer is much more common in Saudi Arabia in comparison to the West. There is a worldwide increase in the incidence of thyroid cancer. The objective of this study is to highlight in details the wide spectrum of histopathologic diagnosis encountered in patient undergoing thyroid surgery in the population of Riyadh region of Saudi Arabia. Patients and Methods: Retrospective review of all thyroid samples for 256 patients whom underwent thyroid surgery at King Khalid University Hospital, King Saud University, Riyadh, during the period between 2000 and 2009. Of those, 171 cases were non neoplastic and 85 neoplastic lesions. Females constitute 80% of non neoplastic lesions and 79% of all thyroid malignancies. The peak incidence of thyroid cancer was in the third decade. Papillary thyroid carcinoma was the most common cancer (71%). Conclusion: Thyroid cancer is a common cancer in Saudi Arabia; it is the second most common cancer in females. The increasing rates of thyroid cancer occur predominantly in women. Papillary thyroid carcinoma accounted for the bulk of this increase. Additional studies are needed to explain the rise in papillary thyroid carcinoma incidence in Saudi Arab as well as throughout the world and to search potential risk factors that are currently unrecognized.
Keywords: thyroid; diseases; pattern; Saudi Arabia